Questionnaire on Attitudes vis-a-vis Situations of Aggression. Preliminary results of their adaptation to the school environment - Caminos, Verónica (2017)
The Argentine Questionnaire on Attitudes vis-a-vis Situations of Aggression(Moreno y Pereyra, 2000) was adapted to the educational environment. For its preliminary validation, 143 Argentine teachers participated. The items turned out to be discriminative and they were grouped, based on a Factorial Exploratory Analysis, into three dimensions that are related to the theory: Passivity (α = .90), Aggressiveness (α = .95) and Prosocial behavior (α = .92). The constructive validity was also tested by analyzing the hypothesis that confirms teachers with a high level of burnout syndrome have a greater tendency to behave negatively when faced with situations of aggression in the classroom context. These results were also related to the theory (p< .001). Based on these analyses, it is concluded that the preliminary version of the instrument is apt for submission to psychometric studies of a more rigorous nature and wider.